Penerapan Strategi Inside Outside Circle Dalam Upaya Meningkatkan Penguasaan Konsep Dan Hasil Belajar Pada Pembelajaran IPA Kelas V SDN Tlogoharum 02 Wedarijaksa Pati Tahun Ajaran 2014/2015 - Ramadhani, Noor Fitria; , Samino (2015)
This research is a classroom action research conducted in two cycles with the aim of improving the ability of mastery of concepts and student learning outcomes through strategies inside outside circle Each cycle consisted of two meetings, each meeting through two stages: planning, action, observation and reflection. Subject recipient of action was fifth grade students of SDN 02 Tlogoharum totaling 37 students, the subject of the perpetrator is a researcher and teacher. Techniques of collecting data using interviews, observation, documentation, and testing. Variables that are being targeted by researchers is the ability to master concepts and student learning outcomes. Data analysis technique used is an interactive model that has three components: data reduction, exposure data and inference. The results showed an increase in mastery of concepts and learning outcomes of students after a class action was held using the inside outside circle. It can be seen from the students' mastery of the concept of initial conditions for 48.65% increase in the first cycle of 62.16% and 81.08% for the second cycle. Results of study on the initial conditions of 54.05% also increased in the first cycle of 70.27% and the second cycle of 86.48%. Thus it can be seen that learning science using the strategy inside outside circle can improve the mastery of concepts and learning outcomes of students of class V SDN Tlogoharum 02 academic year 2014/2015.